THE MCKINSEY MODEL IN BUMDES INSTITUTIONAL CAPACITY BUILDING STRATEGY - Iqbal, Muh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the role of the McKinsey Model as a strategy for developing institutional capacity for Village Owned Enterprises (BUMDes) in Alastengah Village, Paiton, Probolinggo . The research model is a descriptive research following the strategy of the McKinsey model. The data collection was through observation, interviews and documentation. The results of the study found that programs and business fields managed by BUMDes by regulating business operations and livestock can increase community welfare. The results of the managed business are marketed outside the village so that it helps improve the economy of the Alastengah community. Institutional Capacity Building Development following the McKinsey Model is divided into four stages, these are; a) aspirations: actualizing community welfare through developing economic enterprises, animal husbandry and exploring the potential of village youth human resources. The hope is that the community can become skilled and develop to develop village progress and reduce village unemployment through the formation of BUMDES. b) Strategies: the community is entrusted by the BUMDes to manage livestock with a 'livestock fattening system', in regard to feed for livestock fattening, the food has been provided and specially made by the local BUMDes. The human resources managing BUMDES collaborate with the community to formulate the food so that livestock get fat quickly and harvest quickly. c) Organizational skills: government organizations such as BUMDes need to form management that is truly qualified in their field so that the organization can run smoothly. d) Systems and infrastructure; the institutional development of BUMDES really needs people who are responsible, able to protect the community and competent in carrying out the tasks and functions of daily activities in BUMDES